Base‐Free Iron Catalyzed Transfer Hydrogenation of Esters Using EtOH as Hydrogen Source - Farrar‐Tobar, Ronald A.; Wozniak, Bartosz; Savini, Arianna; Hinze, Sandra; Tin, Sergey; de Vries, Johannes G. (Angewandte Chemie International Edition, 2019)
Herein, we report on the use of the iron pincer complex Iron‐MACHO‐BH, in the base‐free transfer hydrogenation of esters with EtOH as a hydrogen source. More than 20 substrates including aromatic and aliphatic esters and lactones were reduced affording the desired primary alcohols and diols with moderate to excellent isolated yields. It is also possible to reduce polyesters to the diols with this method, enabling a novel way of plastic recycling. Reduction of the renewable substrate methyl levulinate proceeds to form 1,4‐pentanediol directly. The yields are largely governed by the equilibrium between the alcohol and the ethyl ester. Even plastic can be reduced! Transfer hydrogenation of esters and lactones with EtOH can be effected using 5 mol % of Fe‐MACHO‐BH as catalyst. This catalyst does not need any base activation, thus resulting in very high selectivities.